2014
DOI: 10.1016/j.jad.2013.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Auditory M50 and M100 sensory gating deficits in bipolar disorder: A MEG study

Abstract: These findings suggest that bipolar I disorder patients have auditory gating deficits at both pre-attentive and early attentive levels, which might be related to STG structural abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Based on the title and abstract, 24 potentially eligible articles were identified. The two authors conducted a full-text review and determined that 10 articles fulfilled the inclusion criteria (Olincy and Martin, 2005;Carroll et al, 2008;Hall et al, 2008;Sanchez-Morla et al, 2008;Lijffijt et al, 2009;Patterson et al, 2009;Cabranes et al, 2013;Wang et al, 2014;Hall et al, 2015;Vuillier et al, 2015). Six of these studies consisted of more than one comparison, and thus a total of 14 and 8 individual investigations for S2/S1 ratio and S1 À S2 difference score, respectively, were included in the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Based on the title and abstract, 24 potentially eligible articles were identified. The two authors conducted a full-text review and determined that 10 articles fulfilled the inclusion criteria (Olincy and Martin, 2005;Carroll et al, 2008;Hall et al, 2008;Sanchez-Morla et al, 2008;Lijffijt et al, 2009;Patterson et al, 2009;Cabranes et al, 2013;Wang et al, 2014;Hall et al, 2015;Vuillier et al, 2015). Six of these studies consisted of more than one comparison, and thus a total of 14 and 8 individual investigations for S2/S1 ratio and S1 À S2 difference score, respectively, were included in the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Our results show that cortical gating dynamics of STG generators evoked by both the standard and deviant tones demonstrated highly increased strength of both gating components in all subjects lacking PFC generator activity [60]. This result is of extreme clinical importance because the prevalent view of the gating-related pathologies assumes that the larger amplitude of the extracranial gating response to the standard tone (i.e., redundant stimuli) reflects impaired gating out processing of neural substrate in primary auditory areas only (i.e., STG generators) [61][62][63][66][67][68][69]. Our novel results provide strong evidence of sustained inhibitory activity of the PFC generator that suppresses or modulates the activity of the STG generators as an underlying mechanism of both gating phenomena.…”
Section: Functional Mechanisms Underlying Auditory Sensory Gatingmentioning
confidence: 99%
“…Sensory gating deficits have been associated with several clinical conditions. Patients with schizophrenia [62][63][64], Alzheimer's disease [60,64,65], bipolar disorder [66], post-traumatic stress disorder [67], Parkinson's disease [68], or Huntington's disease [69] show alerted sensory gating dynamics compared to controls. Abnormality in extracranially measured auditory gating responses is recognized as one of the best established marks for schizophrenia [70,71].…”
Section: Clinical Correlates Of Sensory Gatingmentioning
confidence: 99%
“…Consequently, the dysfunction of these gating mechanisms ultimately leads to cognitive dysfunction (Venables, ) and behavioral disorders that are related to many neuropsychiatric diseases and psychoses (Morales‐Muñoz et al, ). Sensory gating deficits are associated with the pathophysiology of bipolar disorder (Wang et al, ), post‐traumatic stress disorder (Neylan et al, ), Parkinson's disease (Teo et al, ), Huntington's disease (Uc, Skinner, Rodnitzky, & Garcia‐Rill, ), and depression (Wang et al, ). Although abnormalities in extracranially measured auditory gating responses are recognized as a well‐established trait in patients with schizophrenia (Adler et al, ; Bramon, Rabe‐Hesketh, Sham, Murray, & Frangou, ; Patterson et al, ), recent studies have revealed gating source topology modulation to have a high potential to be an individual biomarker for the detection of Alzheimer's disease (Josef Golubic, ; Josef Golubic et al, ), which may provide a unique opportunity to detect physiological changes associated with the disease before symptoms occur.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous neurophysiological studies have explored the generators underlying gating mechanisms, but there is no agreement on the gating network (Garcia‐Rill et al, ; Grunwald et al, ; Korzyukov et al, ; Thoma et al, ; Yvert, Crouzeix, Bertrand, Seither‐Preisler, & Pantev, ). Range of brain regions have been proposed as the generators of P50/M50 auditory response; predominantly the bilateral superior temporal gyri (STG; Cacace, Satya‐Murti, & Wolpaw, ; Edgar et al, ; Reite, Teale, Zimmerman, Davis, & Whalen, ; Thoma et al, ; Wang et al, ; Yvert et al, ), the frontal cortex only (Garcia‐Rill et al, ; Korzyukov et al, ), the frontal cortex in addition to the parietal, temporal and cingulate areas (Boutros, Gjini, Eickhoff, Urbach, & Pfliegerd, ; Boutros, Gjini, Urbach, & Pflieger, ), but also the hippocampus, thalamus and frontal cortex along (Tregellas et al, ; Williams, Nuechterlein, Subotnik, & Yee, ). Proposed involvement of subcortical regions in the generation of P50/M50 response has been demonstrated with functional magnetic resonance imaging (fMRI; Tregellas et al, ) or with fMRI‐guided EEG source‐localization (Williams et al, ), although later attempts failed to replicate their results (Mayer et al, ).…”
Section: Introductionmentioning
confidence: 99%